Reflective Journal: The Learners’ Perspective in Formal Instruction - May-Melendez, Rosa; Balderas-Garza, Myrna; Alcocer-Vazquez, Eloisa; Quijano-Zavala, Gandy (European Scientific Journal, ESJ, 2019)
As part of the evaluation process, some strategies are implemented to foster students’ learning in the English Language Teaching Degree. Professors from a Universidad Autónoma located in the South part of Mexico are conducting action research based on the new educational model in which reflective journal is one of those strategies to be developed, therefore, a study based on the use of reflective journal learning in a course was carried out. The purpose was to investigate if learners find it useful during their learning process and their willingness to use it in all courses. In order to gather data, researchers designed a weekly reflection sheet where students were asked to provide their reflections about the topics and the difficulties found during the summer course, which is a course from the curricula. After the analysis of the information, researchers noticed that students found the use of reflective journals productive for their learning; however, they do not want to use them in all the courses. In conclusion, although reflective journals from students’ perspectives are useful, it is a strategy that requires time and they do not want to use them for all the courses, hence the professors will have to vary this strategy among the courses.